Development and Characterization of Novel Nanofibrous Metal–Organic Framework Adsorption Membranes for Water Treatment - Efome, Johnson Effoe (Université d'Ottawa / University of Ottawa, 2018)
Membrane technology has become a predominant process in providing one of the key components of life (water), either through water and wastewater treatment for water quality purposes or desalination as seen in Ultra-filtration, Nano-filtration, Reverse osmosis, Membrane distillation, Pervaporation, among others. With the ever-increasing demand for portable water due to population increase, constant research has focused on the improvements of the performances of the different water treatment systems including enhancing the performance of the membrane. Among all the different membrane performance enhancement techniques exploited, incorporation of filler has gained much grounds in the last decades. Traditional fillers like silica gel, activated carbon, metal oxides and zeolites are now being challenged by the recent class of mesoporous materials known as Metal Organic Frameworks (MOFs), which are built of metal ions or metal ion clusters linked together by organic ligands giving these materials tunable pore geometries and pore volume, greatly improved surface area with extraordinary adsorptive properties. The membrane incorporating MOFs demonstrate enhance performances more than the other fillers due to the good coordination of the organic moiety and polymers. The overall objective of this project is to develop and study a membrane incorporated MOFs nanofiber system vis-à-vis their applications in heavy metal contaminated water treatment, stability in aqueous media and the advantages and drawbacks of these composite membranes with regards to the quality of the water produced. The developed materials were characterized by SEM, FTIR, TEM, XPS, DSC, and TGA. The heavy metals earmarked for this study include; Lead, Mercury, Cadmium, and Zinc and were studied using flame atomic absorption spectrometry (FAAS). Upon successful fabrication of the nanofiber membranes, detailed adsorption studies were conducted (pristine MOF, pristine nanofibers, enmeshed MOFs) to establish adsorption kinetics and isotherm, which were used further to select the best performing membranes for filtration application. Two different MOFs were used, MOF808; made of Zirconium and Benzene Tricarboxylate) and MOF F300; made of Iron and Benzene Tricarboxylate) The adsorption capacities of the MOFs for the different heavy metal analyzed were; MOF 808 (Pb-170.74 mg g-1, Zn-287 mg g-1, Cd-225.05 mg g-1, Hg-276.96 mg g-1) and MOF F300 (Pb-148.13 mg g-1, Hg-229.66 mg g-1), while the membrane adsorption capacities were; PA808 (MOF 808 embedded within polyacrylonitrile (PA) nanofibers, (Pb-23.98 mg g-1, Hg-50.88 mg g-1), PA300, MOF F300 embedded within polyacrylonitrile nanofibers, (Pb-30.19 mg g-1, Hg-53.09 mg g-1). Upon activation of MOF 808 by water (hydractivation), the removal efficiency of MOF 808 was improved by 10% while the MOF membrane efficiency was increased by 30%. Filtration experiments could produce 577.5 L of treated water with a single layer of PAN/ MOF808 membrane at 0.1 bar using a 50 ppb Pb ion feed solution.
Keywords: Metal-organic frameworks; water treatment; Heavy metals; membrane adsorption; membrane filtration; breakthrough curves